INCLUSIVITY OF GREEN CRIMES IN THE INDIAN ENVIRO-LEGAL REGIME – NEED OF THE HOUR (International Journal of Food and Nutritional Sciences, 2022)
Nature has given us the environment in its purest form and we, being the guardians have failed totake this responsibility on our shoulders. Our failure lies not only in the rampant increase inenvironmental wrongs but the rise of crimes in this domain.